Peningkatan Pengetahuan Remaja Tentang Kesehatan Mental Melalui Program Konseling Keliling - Bachri, Syaiful; Rahmat, Rezqiqah Aulia; Thalib, Kiki Uniatri; Malaha, Naomi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Adolescent mental health is a critical issue that requires special attention, given the increasing incidence of anxiety, depression, and risky behaviors in this age group. Limited access to counseling services and adolescents' low understanding of mental health are major challenges, especially in areas with limited health services. This community service program aims to increase adolescents' knowledge and awareness of mental health through a Mobile Counseling Program. The program was conducted in three secondary schools within the target area, involving 120 adolescents aged 13–18. The methods used included outreach, group counseling, individual counseling, and distribution of educational media. Evaluation was conducted through pre- and post-tests to measure knowledge gains and participant satisfaction questionnaires. The results showed a significant increase in adolescents' knowledge, with an average pre-test score of 58.4 increasing to 84.2 in the post-test. Ninety-two percent of participants stated that the mobile counseling program was very beneficial and should be conducted regularly. In conclusion, the Mobile Counseling program is effective in increasing adolescents' knowledge and awareness of mental health. This activity is recommended as a sustainable program in schools and communities to strengthen preventive efforts against mental health issues.